Spirituality as moral effort in the world of paradoxicality of the informational time - Zuyev, Andriy (Actual Problems of Mind, 2017)
The author sets the task of explore the possibility of determination and theoretical usage of such concepts that designate various levels of the human life in the environment of the informational-temporal direction. The main conclusion is that spirituality in the modern world is only a sign of this or that informational reality which is destined for a certain consumer function.